A path to decolonization? Reducing air travel and resource consumption in higher education. (January 2022) - Nevins, Joseph; Allen, Stephen; Watson, Matt
Highlights: Explores how academic flying emerges from and reproduces colonial relations. Considers how a decolonial lens enriches our understanding of academic flying. Advocates for a centering of nature in projects of decolonization. Argues for a common project of decolonization and a far-reaching reduction in academic flying as part of a common project of socio-ecological justice for all. Abstract: From "flight shame" or flying consciousness to Stay Grounded and FlyingLess, calls for, and organized efforts to achieve, a marked decrease in flying in response to intensifying climate crisis abound. Of particular concern are frequent flyers, among whom are many in academia, especially in the high-income parts of the world. One manifestation is the proliferation of scholarship that critically analyzes academic flying while advocating for slower forms of travel, new forms of research and collaboration, and a low-greenhouse-gas-emitting academy more broadly. This conceptual article builds on that scholarship by engaging the growing literature calling for the decolonization of higher education institutions and the broader world. In doing so, and by attempting to bring into conversation two currently disconnected streams of literature, it explores how academic air travel both reflects and helps to reproduce patterns of colonial relations. Relatedly, the article considers how flying less contributes to the decolonization of higher education—especially in relation to "nature" and the appropriation of "the commons." By insisting on the inextricable entanglement of society and nature, it thus illuminates how aeromobility-related consumption both arises from and reproduces persistent inequities born of imperialism and coloniality. On this basis, the article pushes advocates of reduced flying and of decolonization to engage one another in a common project to challenge disparities between peoples and places, as well as interspecies ones, as they relate to aeromobility, consumption, and political ecology.